The Impact of The Terminal Inspection Unit's Rapid Response in Mitigating Baggage Handling System Constraints on OTP (On-Time Performance) at Juanda International Airport Terminal 2 - Rizqi Firmansyah Bibra; Mei Retno Adiwati (Majapahit Journal of Islamic Finance and Management, 2025)
Airport operational performance is highly dependent on the reliability of its supporting facilities, one of which is the Baggage Handling System (BHS). Disruptions to the BHS have the potential to interfere with On-Time Performance (OTP) and passenger satisfaction. This qualitative study aims to analyze the impact of the Terminal Inspection (TI) Unit's rapid response in mitigating BHS constraints on OTP at Terminal 2 of Juanda International Airport. Data was collected through field observations and in-depth interviews with three key parties, namely the Terminal Inspection Unit, the Mechanical Unit, and representatives from Singapore Airlines. The results show that despite not having written standard procedures, the TI Unit has implemented a quick and effective response by acting as a central coordinator. Coordination between units is considered excellent through layered communication channels, although there are differences in perception regarding work pressure. BHS disruptions have not directly caused significant flight delays thanks to contingency procedures, but they have the potential to indirectly affect OTP through domino effects such as long queues and a decline in service quality. This study recommends the development of written SOPs, crisis communication training, and the strengthening of an integrated monitoring system to improve airport operational resilience.